Computational and Experimental Prediction of Human C-Type Lectin Receptor Druggability - Aretz, Jonas; Wamhoff, Eike-Christian; Hanske, Jonas; Heymann, Dario; Rademacher, Christoph (Frontiers in Immunology, 2014)
Mammalian C-type lectin receptors are involved in many aspects of immune cell regulation such as pathogen recognition, clearance of apoptotic bodies and lymphocyte homing. Despite a great interest in modulating C-type lectin receptor recognition of carbohydrates, the number of specific molecular probes is limited. To this end, we predicted the druggability of a panel of 22 C-type lectin receptors using DoGSiteScorer. The computed druggability scores of most structures were low, characterizing this family as either challenging or even undruggable. To further explore these findings, we employed a fluorine-based NMR screening of fragment mixtures against DC-SIGN, a receptor of pharmacological interest. To our surprise, we found many fragment hits associated with the carbohydrate recognition site (hit rate = 13.5%). An SPR-based follow-up assay confirmed 18 of these fragments (47%) and equilibrium dissociation constants were determined. Encouraged by these findings we expanded our experimental druggability prediction to Langerin and MCL and found medium to high hit rates as well, being 15.7% and 10.0%, respectively. Our results highlight limitations of current in silico approaches to druggability assessment, in particular with regard to carbohydrate-binding proteins. In sum, our data indicate that small molecule ligands for a larger panel of C-type lectin receptors can be developed.